PENINGKATAN HASIL DAN AKTIVITAS BELAJAR PADA MATERI JARINGAN MAKHLUK HIDUP MELALUI MODEL PEMBELAJARAN GUIDED INQUIRY LEARNING - Nurhayati, Evi (Persatuan Guru Republik Indonesia Kota Semarang, 2022)
This classroom action research aims to examine the effect of guided inquiry learning on improving learning outcomes and learning activities of students in class XI MIPA 1 SMA Negeri 6 Semarang. In this study, the research subjects were students of class XI MIPA 1 SMA Negeri 6 Semarang. Data collection techniques in this study include classroom observations, interviews, distributing questionnaires, formative evaluations, and discussions with partner teachers (collaborators). While the data analysis used in this study is a quantitative and qualitative data analysis technique. The application of the guided inquiry learning learning model can improve scientific literacy skills with an indicator of success, namely the results of scientific literacy students in the class in Cycle I are able to achieve an average score of each aspect, namely 75% or on good criteria and in Cycle II it increases to an average score every aspect that is 85% or on very good criteria. The results showed that the average value classically increased from 68 in Cycle I to 80 in Cycle II and the percentage of students who were able to meet the minimum completeness criteria in Cycle II had reached 89%. Student learning activities also increased as seen from the activity of asking questions which increased from a score of 14 in Cycle I to a score of 29 in Cycle II or an increase of 41.67%. The activity of answering questions increased from a score of 18 in Cycle I to a score of 27 in Cycle II or an increase of 25%. Meanwhile, the activity of doing the task increased from a score of 23 in Cycle I to a score of 32 in Cycle II or an increase of 25. All the results of the action had reached the expected criteria. Based on the results of the classroom action research that has been carried out, it is concluded that guided inquiry learning is assisted by Liveworksheet media which is able to improve the scientific literacy skills of class XI MIPA 1 SMA Negeri 6 Semarang